Fallout : the Hiroshima cover-up and the reporter who revealed it to the world - Blume, Lesley M. M. (Simon & Schuster, 2020)
"New York Times bestselling author Lesley M.M. Blume reveals how a courageous reporter uncovered one of greatest and deadliest cover-ups of the 20th century--the true effects of the atom bomb--potentially saving millions of lives"--